Successful Treatment of Relapse Cutaneous Tuberculosis on Pregnant Woman with Ethambutol Allergic - Jahja T Widjaja; Dian Puspitasari; Evelyn Nathania (Universitas Kristen Maranatha, 2023)
Tuberculosis infection among pregnant women often reveals unspecific clinical manifestations, and cutaneous tuberculosis is a rare form of extrapulmonary tuberculosis. The aim of this case report is to manage well Extra-Pulmonary tuberculosis manifestation, especially in pregnant women. A Pregnant woman with a gestational age of 6-7 weeks complained of red spots on cheeks. One year ago, the patient suffered cutaneous tuberculosis and was only treated with Rifampicin, Isoniazid, and Levofloxacin; pyrazinamide and ethambutol were not given due to a strong suspicion of allergy. Physical examination revealed plaque with scales, and PCR examination revealed Mycobacterium tuberculosis. She suffered relapse of cutaneous tuberculosis and was given rifampicin, isoniazid, and pyrazinamide. After 2 weeks the skin lesion improved significantly, and ethambutol was added to the regimen. The patient suffered from drug eruption, ethambutol was discontinued, and the skin lesion disappeared after four months of treatment. The regiment was continued for one year; showed better condition and delivered a healthy baby boy. Cutaneous tuberculosis is a rare form of extrapulmonary tuberculosis (1-1.5%) and is hard to diagnose and treat, especially in pregnant women. Allergic to one of its drugs can increase its risk of being resistant and increase its mortality and morbidity. As conclusion, prompt treatment is needed for tuberculosis patients, especially pregnant women. Early detection and examinations are required to diagnose it properly.